Novel bioactive extract from yarrow obtained by the supercritical antisolvent-assisted technique inhibits lipid metabolism in colorectal cancer - Gómez de Cedrón, Marta; Siles-Sanchez, Maria de las Nieves; Martín-Hernandez, Diego; Jaime, Laura; Santoyo, Susana; Ramírez de Molina, Ana (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Altered lipid metabolism in cancer is associated to dissemination and prognosis. Bioactive compounds naturally occurring in Achillea millefolium L. (yarrow) have been reported to exert antitumour activities. Food biotechnology may provide on-demand mixtures of bioactive compounds with complementary activities in cancer treatment. Methods: Supercritical-antisolvent-precipitation (SAS) has been applied to fractionate the bioactive compounds from an Ultrasound-Assisted-Extraction yarrow extract resulting in two extracts with distinct polarity, yarrow-precipitate-(PP) and yarrow-separator-(Sep). Total phenolic content and relevant essential oils have been characterized. Antioxidant, anti-inflammatory and antiproliferative activities have been compared. Moreover, the effect on the inhibition of colorectal cancer cells’ bioenergetics has been evaluated. Results: Yarrow-PP exerted the highest antioxidant activity, even higher than the complete UAE-yarrow extract, meanwhile yarrow-Sep showed the highest anti-inflammatory activity, even higher than the complete UAE-yarrow extract. Interestingly, yarrow-Sep inhibited key lipid metabolic targets in CRC cells extensively shown to be implicated in cancer dissemination and prognosis —SREBF1, FASN, ABCA1 and HMGCR— and epithelial to mesenchymal targets—CDH1, ATP1B1, CDH2 and Vimentin—augmenting cell adhesion. Conclusions: In summary, SAS technology has been applied to provide a novel combination of bioactive compounds, yarrow-Sep, which merits further research to be proposed as a potential complementary nutraceutical in the treatment of CRC.